Bread from composite cassava wheat flour. II: effect of cassava genotype and nitrogen fertilizer on bread quality - Shittu, T.; Dixon, A.; Awonorin, S.; Sanni, Lateef O.; Maziya-Dixon, B.B. (Elsevier, 2008)
There is an increasing interest in the use of cassava roots for food and industrial purposes especially in the baking industry in Nigeria. Development of some cassava mosaic disease (CMD) resistant clones and application of inorganic fertilizers are principal strategies targeted in the country to boost and sustain cassava root production and utilization. A study was conducted to determine the effect of cassava genotype and field application of nitrogen fertilizer on some physical properties of bread from composite cassava– wheat (CCW) flour. Five CMD cassava clones were planted in a randomized complete block design with two level of fertilizer treatments (0 and 160 kg nitrogen/ha) with two replications while harvesting was done 12 months after planting. Composite flour was produced at a ratio of 10/90 (cassava/wheat flour, w/w). The oven spring, specific volume, crumb texture (softness) and crumb moisture of loaves ranged from 0.57 to 0.63 cm, 4.37 to 6.85 cm3/g, 18.4 to 29.4 mm and 31.40% to 34.70%, respectively. The crust’s tristimulus color parameters L*, a*, b* and brownness index also ranged from 54 to 67, 9 to 15, 22 to 29, and 57 to 83, respectively. These values differed significantly from each other at p < 0.01. Out of all these loaf properties, crumb texture was the most affected by the main and interactive effects of cassava genotype and fertilizer application (p < 0.001) while loaf weight was only affected by their interactive effects (p < 0.05). Digital image analysis of the bread crumb showed that the total number of cells, number of small cells and total cell area of the bread crumb ranged from about 22 to 27 cm 3, 20 to 25 cm 3 and 12% to 29%, respectively. The distribution of large cells and total cell area occupied in the crumb were principally determined by the genotypic difference (p < 0.05) in the cassava roots. The main effect of fertilizer application significantly affected the distribution of small cells, total number of cell and the cell area (p < 0.05). However, the interactive effects of genotype and fertilizer application was more significant (p < 0.01) on the crumb cell characteristics. The study indicated that optimal quality of CCW bread loaf could be attained by appropriate selection of cassava genotype and fertilizer application.